Effectiveness of Japanese traditional medicine (Kamikihito and Saikokeishito) for treating long COVID: a prospective observational study - Rie Ono; Rie Ono; Rie Ono; Shin Takayama; Shin Takayama; Shin Takayama; Ryutaro Arita; Ryutaro Arita; Ryutaro Arita; Kota Ishizawa; Akiko Kikuchi; Akiko Kikuchi; et al. (Frontiers in Medicine)
BackgroundLong COVID symptoms, especially brain fog, significantly impair patient quality of life (QOL); however, effective treatments remain elusive. Japanese traditional medicine (JTM, usually called Kampo medicine) is often used adjunctively to treat patients with diverse manifestations of long COVID.ObjectiveTo evaluate the effectiveness of JTM in treating long COVID using a comprehensive QOL assessment.MethodsThis single-center, prospective observational study evaluated QOL changes in patients with symptoms persisting beyond 28 days from the onset of COVID-19 (long COVID) who visited our general medicine outpatient department between October 2021 and August 2024. The treatment plan was determined by the attending physician based on the patient’s condition. The health-related QOL (HR-QOL) was comprehensively assessed using EuroQol-5 demensions-5levels (EQ-5D-5L) scores (ranging from −0.025 to 1.000, with higher values indicating better HR-QOL) at baseline and 3 months after the first visit. The formulations and factors associated with QOL changes were analyzed using multivariate logistic regression analyses.ResultsWe analyzed 112 patients. The most common symptoms were fatigue (83.9%). The median (interquartile range) HR-QOL of the entire cohort significantly increased from 0.711 (0.561–0.711) at baseline to 0.833 (0.671–0.890) at 3 months (p < 0.0001); the proportion of patients exceeding the national standard significantly increased from 7.1% to 20.4% (p = 0.0037). The brain fog patients group (50.0%, N = 56), the median (interquartile range) HR-QOL of the entire cohort significantly increased from 0.677 (0.551–0.770) at baseline to 0.750 (0.623–0.846) at 3 months (p < 0.005). However, the proportion of patients achieving the Japanese average HR-QOL did not show improvement significantly. A total of 101 patients (90.2%) were treated with JTM, and a combination of kamikihito and saikokeishito was administered to 20 patients. Multivariate regression analysis revealed that the combination usage was associated with greater improvements in the HR-QOL in all patients (odds ratio 5.4) and brain fog patients’ group (odds ratio 6.1).ConclusionLong COVID treatment involving JTM improved the patients’ QOL at 3 months. The combination of kamikihito with saikokeishito may be a potential treatment option for long COVID. However, a randomized controlled trial is required to confirm its efficacy.